How does the theory of government decentralization support the reform system of province directly manages counties (PDMC) in China? - Su, Tong; Mutalib, Rozita Binti Abdul (Edelweiss Applied Science and Technology, 2024)
This study investigates how the theory of government decentralization underpins the reform of the Province Directly Manages Counties (PDMC) system in China, addressing its challenges and proposing rational solutions. The research aims to explore the theoretical basis of PDMC reform to enhance local governance efficiency and optimize intergovernmental relations. The study employs a qualitative methodology, combining theoretical analysis with a review of relevant policy documents and case studies from provinces such as Zhejiang. The research reveals that while the PDMC reform has improved fiscal and administrative efficiency, it faces significant challenges, including mismatches between fiscal and routine powers, excessive management scope at the provincial level, and unclear intergovernmental responsibilities. By integrating the theory of government decentralization, PDMC reform can achieve better alignment of powers and responsibilities, fostering local autonomy and governance capabilities. The findings offer actionable insights for policymakers to refine the PDMC system, balance intergovernmental relations, and support sustainable local economic and social development.